The Zakat, Economic Growth, and Poverty Alleviation: An Artificial Neural Networks Analysis - Muis, Abdullah Ahadish Shamad; Al Firdausi, Muhammad; Akbar, Chairil; Gamal, Shrouq; Saleh, Haitham (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
This research investigates the multifaceted relationship between zakat, economic growth (GDP), and poverty alleviation in Indonesia using Artificial Neural Networks (ANN). Our findings reveal that zakat has more prominent impact on poverty alleviation than on GDP. In particular, we identify a positive correlation between zakat distribution and GDP in Indonesia, indicating that higher zakat distribution contributes significantly to economic growth. It further reveals a negative correlation between zakat distribution and poverty, consistent with most earlier studies, suggesting that zakat significantly contributes to poverty alleviation in Indonesia. Our findings practically imply the potential economic significance of zakat in human development and solving poverty issues. Our research contributes to the novelty of Islamic philanthropic research with the power of advanced AI algorithms, offering insights that can inform policy decisions.